Geodesign Facing the Urgency of Reducing Poverty: The Cases of Belo Horizonte - Lívia de Oliveira Monteiro; Ana Clara Mourão Moura; Camila Marques Zyngier; Ítalo Sousa Sena; Priscila Lisboa de Paula (Disegnare con, 2018)
Belo Horizonte, as well as other Brazilian cities, takes the challenge to attend the urgency of reducing poverty in precarious settlements. The Municipality has a kind of informal settlements, that were resulted from orchestrated urban recent movements and that are inhabited by low-income families. They are called “urban occupations”. These areas, classified in Belo Horizonte’s Mater Plan as Areas of Special Social Interests, need significant actions to plan and carry out structuring interventions for urban and legal regularization. Methods had to be tested to construct a new way to develop these areas, because they present latent dynamics and redraw over themselves several times. Geodesign methodology was used to organize tables of discussion, co-creation of ideas and composition of proposals through consensus by approximation. DOI: https://doi.org/10.20365/disegnarecon.20.2018.6